An anatomy of IGP and BGP routing protocols - Taha, Imad; Alkandari, Abdulrahman (2012)
Due to the growth of computer networks, the word routing protocol has spread with a notice able speed making a huge impact through the world of networking. Various types of routing protocols have been used in lots of fields; each field uses the protocols that suit its needs with consideration to several metrics such as power and bandwidth consumption. In this paper we propose the idea of routing protocols, starting with an overview of the basics of Interior Gateway Protocols (IGP) and Border Gateway Protocols (BGP). Later, we describe the idea of Link State Routing Protocols (LSRP) and Distance Vector Routing Protocols (DVRP) while making a comparison which should determine the protocol needed for each network topology. The weaknesses and strengths of each routing protocol will be also discussed.